2005
DOI: 10.1364/opex.13.003896
|View full text |Cite
|
Sign up to set email alerts
|

Velocity distribution of Gold nanoparticles trapped on an optical waveguide

Abstract: The velocity distributions of 250nm diameter gold nanospheres trapped in the evanescent fields of optical waveguides are studied. The automated analysis of a large number of particles and temporal frames is described. It is used to show that the envelope of the particles' speed follows the mode intensity profile of the evanescent field along a length of the waveguide and across its width. Modal beating in a dual-moded waveguide is mapped by analysis of nanoparticle distributions above the waveguide. A modal po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Gold nanoparticles of diameters 20-80 nm were propelled in the evanescent wave above the waveguide with a speed of 4-8 mm/s with modal power 500 mW and TM polarization (at a wavelength of 1047 nm) [162,163]. Much bigger gold nanospheres of diameter 250 nm were guided with a velocity up to 500 mm/s with modal power 150 mW at a wavelength of 1066 nm [158]. A small dielectric spherical particle attached to the end of a single mode optical fiber forms the so-called fiber-optic OT that are able, as demonstrated by Numata et al [394], to confine in 2-D gold nanoparticles of sizes 40, 100 and 200 nm against the surface.…”
Section: Manipulation Of Nanoobjectsmentioning
confidence: 99%
“…Gold nanoparticles of diameters 20-80 nm were propelled in the evanescent wave above the waveguide with a speed of 4-8 mm/s with modal power 500 mW and TM polarization (at a wavelength of 1047 nm) [162,163]. Much bigger gold nanospheres of diameter 250 nm were guided with a velocity up to 500 mm/s with modal power 150 mW at a wavelength of 1066 nm [158]. A small dielectric spherical particle attached to the end of a single mode optical fiber forms the so-called fiber-optic OT that are able, as demonstrated by Numata et al [394], to confine in 2-D gold nanoparticles of sizes 40, 100 and 200 nm against the surface.…”
Section: Manipulation Of Nanoobjectsmentioning
confidence: 99%
“…Meandering of the trapped particle was observed as the particle moved along the waveguide. As this 2 µm wide waveguide was multimode, the meandering is caused by multimode interference [19,20]. In the loop-section, the waveguides were 1.3 µm wide and single-mode.…”
Section: Tracking Of Particles On Top Of Straight Planar Waveguidesmentioning
confidence: 99%
“…Gold nanoparticles have a high scattering cross-section compared with latex particles and biological cells and have potential as tags in sorting of biological species. Hole et al (2005) trapped and propelled 250 nm diameter gold spheres; individual particle trajectories exhibited velocities up to 500 lm/s, showing promise for high throughput sorting. Recently Schroll et al (2007) have demonstrated bulk transport of liquid with mesoscopic spatial variations in refractive index under radiation pressure.…”
Section: Evanescent Field Trapping and Propulsionmentioning
confidence: 99%